How Does Workplace Helping Behavior Step Up or Slack Off? Integrating Enrichment-Based and Depletion-Based Perspectives. (March 2020) - Lin, Weipeng; Koopmann, Jaclyn; Wang, Mo
Although helping behavior at work is widely studied, little is known about the processes via which help providers increase or decrease their helping behavior. In the current research, we integrated both enrichment-based and depletion-based perspectives on helping with Kahn's psychological conditions for engagement to offer more comprehensive understanding of how helping behavior may change. Specifically, based on Kahn's model, we simultaneously consider the beneficial effects of helping on help providers' psychological meaningfulness and psychological safety along with the detrimental effects of helping on help providers' psychological resource availability in order to uncover the differential processes through which helping behavior may change. To test our theoretical model, we collected data from a sample of 375 employees using a three-wave time-lagged design. Supporting the enrichment-based perspective, our results demonstrated that employees' helping behavior was positively related to increases in their psychological meaningfulness and psychological safety. Supporting the depletion-based perspective, results showed that helping behavior was also positively related to increases in emotional exhaustion, an indicator of psychological resource availability. Whereas psychological meaningfulness and psychological safety were, in turn, positively related to increases in job involvement, emotional exhaustion was negatively related to increases in job involvement. Finally, job involvement was positively related to subsequent increases in employee helping behavior. We discuss the implications of our findings for both theories and practices.